Study of tissue engineered vascularised oral mucosa-like structures based on ACVM-0.25% HLC-I scaffold in vitro and in vivo - Minyue Zhou; Xiao Chen; Yanling Qiu; He Chen; Yaoqiang Liu; Yali Hou; Minhai Nie; Xuqian Liu (Artificial Cells, Nanomedicine, and Biotechnology, 2020)
Purpose To explore the feasibility of constructing tissue-engineered vascularised oral mucosa-like structures with rabbit ACVM-0.25% HLC-I scaffold and human gingival fibroblasts (HGFs), human gingival epithelial cells (HGECs) and vascular endothelial-like cells (VEC-like cells).Method Haematoxylin and Eosin (H&E) staining, immunohistochemical, immunofluorescence, 5-ethynyl-2′-deoxyuridine (EdU) staining and scanning electron microscope (SEM) were performed to detect the growth status of cells on the scaffold complex. After the scaffold complex implanted into nude mice for 28 days, tissues were harvested to observe the cell viability and morphology by the same method as above. Additionally, biomechanical experiments were used to assess the stability of composite scaffold.Results Immunofluorescence and Immunohistochemistry showed positive expression of Vimentin, S100A4 and CK, and the induced VEC-like cells had the ability to form tubule-like structures. In vitro observation results showed that HGFs, HGECs and VEC-like had good compatibility with ACVM-0.25% HLC-I and could be layered and grow in the scaffold. After implanted, the mice had no immune rejection and no obvious scar repair on the body surface. The biomfechanical test results showed that the composite scaffold has strong stability.Conclusion The tissue-engineered vascularised complexes constructed by HGFs, HGECs, VEC-like cells and ACVM-0.25% HLC-I has good biocompatibility and considerable strength.